Henrico Zucalli in Rome: New Archival Evidence - Gudelj, Jasenka (Array, 2014)
The article describes previously unknown Roman period of Henrico Zuccali (c. 1642–1729), the architect of the Bavarian court in the last quarter of the 17th century, on basis of archival documents from Dubrovnik state archive.